The role of sport in world cinema as a socio-political tool - Kolobova E.Yu. ,; Rubtsova M.V. ,; Pavenkov V.G. , (Theory and Practice of Physical Culture, 2025)
Objective of the study is to determine the significance of sport at the international level, including its growing importance and influence on media societies as a political tool. Methods and structure of the study. Based on an analysis of literary and statistical international databases, a comparative analysis was conducted, combining quantitative and qualitative methods to study the place of sport in European and Russian cinema and its connection with broader political and ideological messages. Media texts from national federal media served as the empirical basis. Results and conclusions. The theme of sport in cinema emerged with the creation of documentary filmmaking and the development of scientific and technological progress, sport and culture. The sports genre has become a leading genre in world cinema, coexisting with other film genres. Sports films reflect social changes, public demands and the culture of individual nations. In each country, a particular sport dominated at a certain period of time, and the Olympic Games were the apogee of the politicization of international sporting competitions, which left its mark on the content of films. Films on this subject are a tool for competition between countries, not only at the Olympic Games, but also in the cinema space, based on the number of films produced and their influence on European society, as confirmed by research into European and Russian sports cinema. The film projects themselves are aimed at generating audience interest in leading a healthy lifestyle and participating in amateur sports. At the federal level, sports films play another important role in articulating and affirming existing power structures and ideological hegemony in Russian society, especially during a particularly difficult period of national and international instability and controversy.